Sport leadership in the 21st century - Borland, John F.; Kane, Gregory M.; Burton, Laura J. (Jones and Bartlett Learning, 2015)
Sports Leadership in the 21st Century provides students with the most current and comprehensive understanding of leadership in sport management. Authored and contributed by leading sport management researchers and practitioners, this text immerses students in the learning process through case studies, interviews with leaders in the sport industry, critical thinking questions, and rich content